2019
DOI: 10.1074/jbc.ra118.006225
|View full text |Cite
|
Sign up to set email alerts
|

Unicellular ancestry and mechanisms of diversification of Goodpasture antigen–binding protein

Abstract: The emergence of the basement membrane (BM), a specialized form of extracellular matrix, was essential in the unicellular transition to multicellularity. However, the mechanism is unknown. Goodpasture antigen-binding protein (GPBP), a BM protein, was uniquely poised to play diverse roles in this transition owing to its multiple isoforms (GPBP-1,-2, and-3) with varied intracellular and extracellular functions (ceramide trafficker and protein kinase). We sought to determine the evolutionary origin of GPBP isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Phylogenetic analysis suggested that all multicellular animals have clear homologues of CERT/GPBP∆26, but that CERT L /GPBP has appeared from vertebrates in the evolution of life . No clear homologue of CERT has been found in plants, protists (or protozoan), fungi or bacteria.…”
Section: Evolutional Aspects Of Certmentioning
confidence: 99%
“…Phylogenetic analysis suggested that all multicellular animals have clear homologues of CERT/GPBP∆26, but that CERT L /GPBP has appeared from vertebrates in the evolution of life . No clear homologue of CERT has been found in plants, protists (or protozoan), fungi or bacteria.…”
Section: Evolutional Aspects Of Certmentioning
confidence: 99%
“…Revert et al reported that CERT L , but not CERT, is exported from cells via a nonconventional secretory pathway [40,52]. Phylogenetic studies have suggested that clear paralogs of human CERT are present widely or ubiquitously in multicellular animals but are absent in other organisms [11,53]. Darris et al proposed that CERT/GPBP∆26 originated in the putative last common unicellular ancestor of metazoans, choanoflagellates, and filastereans during the evolution of life [53].…”
Section: Structure Of Cert and Its Splicing Variantsmentioning
confidence: 99%
“…Phylogenetic studies have suggested that clear paralogs of human CERT are present widely or ubiquitously in multicellular animals but are absent in other organisms [11,53]. Darris et al proposed that CERT/GPBP∆26 originated in the putative last common unicellular ancestor of metazoans, choanoflagellates, and filastereans during the evolution of life [53]. It should also be noted that, although both GPBP and GPBP∆26 were originally reported to be atypical serine/threonine kinases [50,51], this assignment remains controversial because they do not have the signature sequence usually found in serine/threonine kinases [11,53].…”
Section: Structure Of Cert and Its Splicing Variantsmentioning
confidence: 99%
“…These two apparently unrelated functions fed strong controversy over the biological role of the GPBP gene, now reconciled by the realization that this is a remarkable example of a multifunctional protein (10). By comparing transcriptomic and genomic data from some metazoans and unicellular relatives, Darris et al (9) have found that GPBP-2 is the most ancient isoform, already present in choanoflagellates and filastereans. In contrast, GPBP-1 was only observed in chordates.…”
mentioning
confidence: 99%
“…intracellular ceramide transporter and extracellular kinase functions, coexist. They then hypothesized that genomic events taking place at the origin of vertebrates, with the insertion of the 26-amino-acid domain, gave rise to GPBP-1, and, from that point on, both isoforms specialized in their specific roles (9). As occurred with other ECM components, including some BM constituents, further refinements in protein families provided higher vertebrates with novel variants, such as a third GPBP form, GPBP-3, that significantly contributed to the expansion and diversity of BM.…”
mentioning
confidence: 99%